Android application for car maintenance - Raja Nurfarahin Farhanah, Raja Abdul Halim (2019)
Management records and details information of the car maintenance are the crucial part for every car owner to retain the car in good condition. To keep track of the car's condition, there are several mobile applications help to record your vehicles part numbers, maintenance, and fuel consumption. However, there is a common problem faced by the user when using the applications related to backup-related problems. The purposes of this project are to develop a car maintenance application that applies aesthetic and minimalist design and customizability features. This project also aims to evaluate the effectiveness of the car maintenance application by using User Acceptance Testing (UAT). The methodology used for this study is Agile Methodology that allows this mobile application to be flexible developed and manage to respond to any modification made even during system development. To ensure this application fulfil the user requirement, this application is tested by using User Acceptance Test (UAT) which is also to track any error or improper way of a system behaviour so that correction can be made before implementation. The result of the study is the implementation of the Android Application for Car Maintenance. Other than aesthetic and minimalist user interface design, this application also provides user Cloud Backup using Dropbox.